Modulation in the Stiffness of Specific Muscles of the Quadriceps in Patients With Knee Osteoarthritis and Their Relationship With Functional Ability - Chang, Tian-Tian; Zhu, Yuan-Chun; Li, Zhe; Li, Feng; Li, Ya-Peng; Guo, Jia-Yi; Wang, Xue-Qiang; Zhang, Zhi-Jie (Frontiers in Bioengineering and Biotechnology, 2022)
Deficits in the flexibility of the quadriceps are one of the risk factors for developing knee joint disorders. No studies have investigated the changes in the stiffness of the quadriceps muscle among patients with knee osteoarthritis (OA). Therefore, the purpose of this study was to investigate changes in the stiffness of specific-muscle of the quadriceps in patients with knee OA and their relationship with functional ability. Twenty-five patients with knee OA and 25 healthy, asymptomatic subjects were recruited in this study. The stiffness of the vastus lateralis (VL), vastus medialis (VM) and rectus femoris (RF) in all participants was evaluated using MyotonPRO at 60° and 90° flexion of the knee joint. The results of this study showed a greater VL stiffness in patients with knee OA than in healthy subjects at both 60° and 90° of knee flexion (P < 0.05). Significant differences in VL, VM and RF stiffness were obtained at different knee joint angles in individuals with and without knee OA (P < 0.05). In addition, there was a positive correlation between VL stiffness and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores in patients with Knee OA (60° of knee flexion: r=0.508, P=0.010; 90° of knee flexion: r=0.456, P=0.022). These results indicate that there is an increase in VL stiffness in patients with knee OA compared with healthy, asymptomatic subjects, and the quadriceps stiffness was increased with knee flexion in both healthy subjects and patients with knee OA. VL stiffness is associated with WOMAC scores in patients with knee OA.